A Study Protocol for Increasing Access to Smoking Cessation Treatments for Low-Income Minority Smokers - Matthews, Alicia K.; Watson, Karriem S.; Duangchan, Cherdsak; Steffen, Alana; Winn, Robert (Frontiers in Public Health, 2021)
Background: Smoking rates among low-income patients are double those of the general population. Access to health care is an essential social determinant of health. Federally qualified health care centers (FQHC) are government-supported and community-based centers to increase access to health care for non-insured and underinsured patients. However, barriers to implementation impact adherence and sustainability of evidence-based smoking cessation within FQHC settings. To address this implementation barrier, our multi-disciplinary team proposes Mi QUIT CARE (Mile Square QUIT Community-Access-Referral-Expansion) to establish the acceptability, feasibility, and capacity of an FQHC system to deliver an evidence-based and multi-level intervention to increase patient engagement with a state tobacco quitline. Methods: A mixed-method approach, rooted in an implementation science framework of RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance), will be used in this hybrid effectiveness-implementation design. We aim to evaluate a novel delivery system (patient portal) for increasing access to smoking cessation treatment. Consistent with clinical practice guidelines, the following evidence-based interventions have been selected for implementation and testing: 1) a brief smoking cessation intervention delivered via a patient portal, 2) proactive linkage of smokers to the Illinois Tobacco Quitline, and 3) patient navigation to reduce barriers to treatment engagement. The RE-AIM framework will be used to evaluate the implementation and sustainability of the intervention. Discussion: This study provides a model for developing and implementing smoking and other health promotion interventions for low-income patients delivered via patient health portals. If successful, the intervention has important implications for addressing a critical social determinant of cancer and other tobacco-related morbidities.